Prior Informed Consent and Traditional Knowledge Systems : EquitableBenefit Share over Biocultural Diversity of Northeast India (Indian Journal of Extension Education, 2010)
The primary objective of this paper is to implement prior informed consent (PIC) and explore the opinion of Adi, Monpa and Khasi communities of Northeastern India over the terms and conditions regarding benefit shares accruing from indigenous knowledge relating to local biodiversity. Study was conduced among purposively selected study areas, community and traditional knowledge holders (TKH). Personal interview method was used primarily to record the data from TKH, The village, regional and state level workshops were organized complimentarily to cross validate the data recorded from TKH. The results indicate that women TKH were more competent in preparation of medicinally important foods, beverages, preservation of foods, ethnomedicines and local agricultural practices, while male TKH were experienced comparatively more in ethnomedicines for human and animals and agricultural practices. TKHs belong to high altitude surrounded by rich forest biodiversity, posses high level of ethics in using and conserving local biodiversity and share the probable benefits with community members. In general, the male knowledge holders were in opinion to mange and use the benefits of traditional practices through Panchayat while female were interested to process it through their indigenous institutions like Kebang, Darbar, Chhoppa, etc. Materialist and non-materialist two major types of incentives were identified to the TKH. At the initial stage of benefits accruing from traditional knowledge, giving non materialist benefits to knowledge holders was found to be more important. TKH living in rich biodiversity areas at high altitudes opinioned to get more benefit percentage towards the welfare and conservation of community based biodiversity.